This action might not be possible to undo. Are you sure you want to continue?

BooksAudiobooksComicsSheet Music### Categories

### Categories

### Categories

Editors' Picks Books

Hand-picked favorites from

our editors

our editors

Editors' Picks Audiobooks

Hand-picked favorites from

our editors

our editors

Editors' Picks Comics

Hand-picked favorites from

our editors

our editors

Editors' Picks Sheet Music

Hand-picked favorites from

our editors

our editors

Top Books

What's trending, bestsellers,

award-winners & more

award-winners & more

Top Audiobooks

What's trending, bestsellers,

award-winners & more

award-winners & more

Top Comics

What's trending, bestsellers,

award-winners & more

award-winners & more

Top Sheet Music

What's trending, bestsellers,

award-winners & more

award-winners & more

Welcome to Scribd! Start your free trial and access books, documents and more.Find out more

**Determine the order and degree of each diﬀerential equation, and whether it is linear or non-linear: (a) x
**

2d

dy y + x + 2y = sin x 2 dx dx d2 y dy + x + y = 8ex 2 dx dx

2

(b) (1 + y 2 )

(c) (d) (e)

**d4 y d3 y d2 y dy + + + +y =2 dx4 dx3 dx2 dx dy + xy 2 = 0 dx dy + xy 2 = 0 dx d3 y dx3
**

2

(f)

+ 4y

dy dx

8

+ y3

d4 y = 3x dx4

2. Verify that the given functions are solution of the respective diﬀerential equations: (a) y = −1 + sin 2x ln(sec 2x + tan 2x) (b) y1 = 1 ln x and y2 = 2 2 x x for for y + 4y = 4 sec2 2x

x2 y + 5xy + 4y = 0, x > 0 4x2 y + 4xy + (4x2 − 1)y = 0, x > 0

sin x cos x (c) y1 = √ and y2 = √ x x

for

3. Show that the equation y 2 − 2y = x3 + 2x2 + 2x + c is a solution of the diﬀerential dy 3x2 + 4x + 2 equation = for some constant c. dx 2(y − 1)

4. Show that the equation y 4 + 16y + x4 − 8x2 = c is a solution of the diﬀerential dy 4x − x3 equation = for some constant c. dx 4 + y3

1

y + 3x = c. 7. 8. y(1) = 2. Verify that the given function is a solution of the given diﬀerential equation for any constant c. For what values(s) of the constant m will the given function be a solution of the given diﬀerential equation? (a) y + y − 6y = 0. Then solve for c so that y satisﬁes the given initial condition: (a) (b) (c) (d) xy − y = x2 . y(1) = 1.5. y = exp(mx) y = xm (b) 2x2 y + 5xy + 4y = 0. 2xyy = y 2 − x2 . given that y = π/4 when x = 0. Find a diﬀerential equation whose general solution is y = c1 e−t/2 + c2 e−2t . Solve the following diﬀerential equations: dy = x ln x2 dx (b) y = x2 ex (a) (c) y = cot 5x dy 1 (d) = 2 dx x (1 − x) dy (e) x(y − 3) = 4y dx dy (f) (1 + x3 ) = x2 y. y = x2 + cx. x2 + y 2 = cx. x ln y ln x y + 1 = 0. dx dy (i) x2 (y + 1) + y 2 (x − 1) =0 dx 2 . (y )2 + 2y − 3 = 0. y(ln y − 1) + ln(ln x) = c. y(0) = 3. 6. c2 are constants. y(e) = 2. given that x = 1 when y = 2. dx dy (g) x3 + (y + 1)2 =0 dx dy (h) cos y + (1 + e−x ) sin y = 0. where c1 .

Are you sure?

This action might not be possible to undo. Are you sure you want to continue?

We've moved you to where you read on your other device.

Get the full title to continue

Get the full title to continue listening from where you left off, or restart the preview.

scribd